2001
DOI: 10.1074/jbc.m010748200
|View full text |Cite
|
Sign up to set email alerts
|

Functional Characterization of Arginine 30, Lysine 40, and Arginine 62 in Tn5 Transposase

Abstract: Three N-terminal basic residues of Tn5 transposase, which are associated with proteolytic cleavages by Escherichia coli proteinases, were mutated to glutamine residues with the goal of producing more stable transposase molecules. Mutation of either arginine 30 or arginine 62 to glutamine produced transposase molecules that were more stable toward E. coli proteinases than the parent hyperactive Tn5 transposase, however, they were inactive in vivo. In vitro analysis revealed these mutants were inactive, because … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2002
2002
2009
2009

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 26 publications
0
17
0
Order By: Relevance
“…A six-histidine tag with in-frame stop codon was introduced upstream of the glycosylphosphatidylinositol anchor site at amino acid 338 and transformed into yeast strain BJ3505. Protein expression and purification were then performed as described previously (13).…”
Section: S4mentioning
confidence: 99%
“…A six-histidine tag with in-frame stop codon was introduced upstream of the glycosylphosphatidylinositol anchor site at amino acid 338 and transformed into yeast strain BJ3505. Protein expression and purification were then performed as described previously (13).…”
Section: S4mentioning
confidence: 99%
“…The in vitro cleavage of Mos1 adjacent to Arg119, Arg167 and Arg183 is consistent with the action of a protease and may re¯ect a role for protein degradation in vivo. For Tn5 it has been suggested that disengagement of the protein from DNA after transposition may be facilitated in vivo by proteolytic cleavage at Lys40 (Twining et al, 2001). …”
Section: Biochemical Analysis Of the Crystalsmentioning
confidence: 99%
“…2 This combination of Tnp EK/LP and ME-flanked DNAs has resulted in the development of an efficient series of gel shift assays (4) and catalytic assays (2,23) used to study the transposition process. Tn5 in vitro assays have also been used to study C-terminally truncated forms of Tnp EK/LP and fulllength Tnp EK/LP with point mutations added to either the N or C terminus (26,27).…”
Section: Tn5 Transposase (Tnp)mentioning
confidence: 99%